PORTUGAL'S ECONOMIC SITUATION OVER THE LAST 10 YEARS - Toshniyozova Marjona Ikrom Qizi; Ulugmurodov F.F. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: Analyze the recent economic developments in Portugal, particularly in the context of global economic changes. The research aims to assess the country's political and economic approaches, as well as the impacts of global factors, with a focus on post-pandemic recovery. Methods: The methods employed include an analysis of statistical data and macroeconomic indicators to evaluate Portugal's economic policies and fiscal measures. Results: The results indicate that Portugal’s growth prospects until 2030 are promising, with significant developments expected in green energy investments and the tourism sector. Additionally, there is a knowledge gap in accurately assessing the country’s prospects in green energy and technological advancement. Novelty: The novelty of this research lies in its emphasis on the intersection of green energy and technological growth as crucial areas for future economic development. These findings hold substantial importance for economic policy planning, especially in guiding investments toward green technologies and the digital economy.